Optical film, polarizing film, image display device, and liquid crystal display device

The use of a solid silica microsphere-based anti-reflective layer on a (meth)acrylic acid resin film addresses the complexity and cost of hollow silica microsphere production, achieving high-transmittance, low-haze optical films for polarizing and liquid crystal displays.

CN120315074APending Publication Date: 2025-07-15KANEKA CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510053946.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-15
Filing Date
2025-01-14
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The production of hollow silica microspheres is complex and costly, limiting their use in high-transmittance, low-haze optical films due to manufacturing challenges, especially for particles smaller than 100nm, which are needed for transparent applications.

Method used

A film with a solid silica microsphere-based anti-reflective layer on a (meth)acrylic acid resin film, comprising a binder resin with a refractive index of 1.50 or less and solid silica microspheres of 15-90nm, achieving a transmittance of 93% and haze of 2% or less.

Benefits of technology

The solution provides high-transmittance, low-haze optical films suitable for use in polarizing films and liquid crystal displays, enhancing brightness and reducing power consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240801680000051
    Figure BDA0005240801680000051
  • Figure BDA0005240801680000111
    Figure BDA0005240801680000111
  • Figure BDA0005240801680000121
    Figure BDA0005240801680000121
Patent Text Reader

Abstract

The invention relates to an optical film, a polarizing film, an image display device, and a liquid crystal display device. Provided is an optical film in which an antireflection layer is formed on one or both surfaces of a (meth) acrylic resin film containing a (meth) acrylic resin, the antireflection layer containing a binder resin having a refractive index of 1.50 or less with respect to light having a wavelength of 594 nm and solid silica fine particles having an average primary particle diameter of 15-90 nm, the content of solid silica particles in the solid content of the antireflection layer is 30-80 wt%, the total light transmittance of the optical film is 93% or more, and the haze is 2% or less. Also provided are a polarizing film, an image display device, and a liquid crystal display device, each of which is provided with the optical film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical thin film, a polarizing thin film, an image display device, and a liquid crystal display device. Background Art

[0002] A liquid crystal display device generally has two polarizing thin films disposed on both sides of a liquid crystal cell. As the polarizing thin film, a polarizing thin film in which a polarizing element protection thin film for protecting a polarizing element is adhered to both sides of the polarizing element with an adhesive is generally used.

[0003] In recent years, demands for higher brightness and lower power consumption of liquid crystal displays have been gradually increasing, and an increase in the transmittance of the polarizing thin film has been desired. Against this background, an antireflection layer (low refractive index layer) has been proposed to be provided on the polarizing thin film. For example, Patent Document 1 proposes a polarizing plate (polarizing thin film) provided with a primer layer on the backlight unit side of a liquid crystal cell, the primer layer containing hollow fine particles and a water-dispersible low refractive index polymer resin.

[0004] Prior Art Documents

[0005] Patent Documents

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2016-531314 Summary of the Invention

[0007] Problems to be Solved by the Invention

[0008] However, hollow fine particles such as hollow silica fine particles are produced by forming a shell on the outer shell of a core as a template and then selectively removing only the core, and the process is complicated. Therefore, there are problems of high cost and a large environmental burden during manufacturing. In particular, it is difficult to manufacture hollow fine particles having a particle size of 100 nm or less used in fields requiring transparency, and their use is limited from an economic point of view.

[0009] Therefore, an object of the present invention is to provide an optical thin film having a high transmittance and a low haze and including an antireflection layer containing solid silica fine particles, and a polarizing thin film, an image display device, and a liquid crystal display device including the optical thin film.

[0010] Solutions to the Problems

[0011] Specific means for solving the above problems include the following embodiments.

[0012] <1> An optical thin film having an antireflection layer formed on one side or both sides of a (meth)acrylic resin thin film containing a (meth)acrylic resin,

[0013] The above anti-reflection layer contains a binder resin having a refractive index of 1.50 or less for light with a wavelength of 594 nm and solid silica fine particles having an average primary particle diameter of 15 to 90 nm, and the content of the solid silica fine particles in the solid components of the anti-reflection layer is 30 to 80% by weight.

[0014] The total light transmittance of the above optical film is 93% or more and the haze is 2% or less.

[0015] <2>The optical film according to <1>, wherein the Young's modulus of the above binder resin is 200 MPa or less.

[0016] <3>The optical film according to <1> or <2>, wherein the thickness of the above anti-reflection layer is 50 to 300 nm.

[0017] <4>The optical film according to any one of <1> to <3>, wherein the above (meth)acrylic resin film contains a (meth)acrylic resin having a ring structure in the main chain.

[0018] <5>The optical film according to <4>, wherein the above ring structure is at least one selected from a succinimide structure, a lactone ring structure, a maleic anhydride structure, an N-substituted maleimide structure, and a glutaric anhydride structure.

[0019] <6>A polarizing film in which the optical film according to any one of <1> to <5> is laminated on a polarizer via an adhesive layer.

[0020] <7>An image display device including the polarizing film according to <6>.

[0021] <8>A liquid crystal display device including:

[0022] A liquid crystal cell;

[0023] A front-side polarizing film laminated on the visual recognition side of the above liquid crystal cell via an adhesive layer;

[0024] A back-side polarizing film laminated on the side opposite to the visual recognition side of the above liquid crystal cell via an adhesive layer; and

[0025] A backlight unit disposed outside the above back-side polarizing film,

[0026] Each of the above front-side polarizing film and the above back-side polarizing film has a polarizer and polarizer protection films disposed on both sides of the polarizer.

[0027] The polarizer protection film disposed on the backlight unit side of the aforementioned backside polarizing film is an optical film according to any one of <1> to <5>, and the antireflection layer of the optical film is located on the backlight unit side.

[0028] Effects of the Invention

[0029] According to the present invention, it is possible to provide an optical film having a high transmittance and a low haze and including an antireflection layer containing solid silica fine particles, a polarizing film, an image display device, and a liquid crystal display device including the optical film. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a cross-sectional schematic view showing an example of the layer structure of the polarizing film of the present embodiment.

[0031] Figure 2 It is a cross-sectional schematic view showing an example of the layer structure of the liquid crystal display device of the present embodiment.

[0032] Description of Reference Numerals

[0033] 10 Polarizing film, 20 Polarizer, 30 Polarizer protection film, 31 Easy adhesion layer, 32 (Meth)acrylic resin film, 33 Antireflection layer, 40 Polarizer protection film, 41 Easy adhesion layer, 42 (Meth)acrylic resin film, 51, 52 Adhesive layer, 100 Liquid crystal display device, 110 Liquid crystal cell, 120a, 120b Polarizer, 130a, 130b Polarizer protection film, 131a, 131b Easy adhesion layer, 132a, 132b (Meth)acrylic resin film, 133a, 133b Antireflection layer, 140a, 140b Polarizer protection film, 141a, 141b Easy adhesion layer, 142a, 142b (Meth)acrylic resin film, 151a, 152a Adhesive layer, 160a Front-side polarizing film, 160b Back-side polarizing film, 170a, 170b Adhesive layer, 180 Backlight unit DETAILED DESCRIPTION OF THE EMBODIMENTS

[0034] Hereinafter, an embodiment of the present invention will be described, but the present invention is not limited to this embodiment. In this specification, the expression "A to B" using numerical values A and B means "A or more and B or less" unless otherwise specified. When a unit is given only to numerical value B in the above expression, the unit also applies to numerical value A. In addition, in this specification, the term "(meth)acrylic" means both "acrylic" and "methacrylic", and the term "(meth)acrylic acid" means both "acrylic acid" and "methacrylic acid". In addition, in this specification, the term "solid silica particles" means "non-hollow silica particles (that is, those obtained by removing hollow silica particles from silica particles)".

[0035] <Optical film>

[0036] The optical film of this embodiment has an antireflection layer containing solid silica particles formed on one or both sides of a (meth)acrylic resin film containing a (meth)acrylic resin. The total light transmittance of the optical film is 93% or more, and the haze is 2% or less. By using such an optical film as a polarizing element protective film, the reflectance of the polarizing film can be reduced and the transmittance can be increased.

[0037] [(Meth)acrylic resin film]

[0038] (Meth)acrylic resin film contains a (meth)acrylic resin as a main component. The content rate of the (meth)acrylic resin in the (meth)acrylic resin film is preferably more than 50% by weight, more preferably 70% by weight or more, further preferably 80% by weight or more, further more preferably 85% by weight or more, and particularly preferably 90% by weight or more.

[0039] (Meth)acrylic resin preferably has a glass transition temperature (Tg) of 120°C or more, more preferably more than 120°C, further preferably 121°C or more, further more preferably 122°C or more, and particularly preferably 123°C or more. When the glass transition temperature of the (meth)acrylic resin is 120°C or more, the dimensional change rate of the (meth)acrylic resin film in a high-temperature environment tends to become smaller. In actual use, (meth)acrylic resin films are mostly laminated with other films. As a result, if the dimensional change rate is small, strain and warping caused by the difference in dimensional change rates with other laminated films can be suppressed.

[0040] For the glass transition temperature, a differential scanning calorimeter (DSC7000X manufactured by Hitachi High-Tech Science Corporation) can be used to measure it at a heating rate of 20°C / minute in a nitrogen atmosphere and obtain it by the midpoint method.

[0041] Here, as the (meth)acrylic resin having a glass transition temperature of 120°C or higher, a (meth)acrylic resin having a ring structure in the main chain can be appropriately used. By using the (meth)acrylic resin having a ring structure in the main chain, heat resistance can be imparted to the (meth)acrylic resin film. As the ring structure, for example, at least one ring structure selected from a succinimide structure, a lactone ring structure, a maleic anhydride structure, an N-substituted maleimide structure, and a glutaric anhydride structure can be mentioned. Among these, from the viewpoints of production simplicity, cost, and quality stability against moisture, a (meth)acrylic resin having a succinimide structure or a lactone ring structure in the main chain is preferred.

[0042] The proportion of the ring structure in the (meth)acrylic resin is preferably 2 to 30% by weight. When the proportion of the ring structure is within the above range, there is a tendency for both the glass transition temperature and the retardation Rth in the thickness direction to be good. The proportion of the ring structure in the (meth)acrylic resin can be calculated by performing weight conversion after determining the molar ratio of the ring structure portion to be measured by 1H-NMR and the portion other than it. 1 H-NMR measurement of the molar ratio of the ring structure portion to be measured and the portion other than it, followed by weight conversion.

[0043] Hereinafter, each ring structure will be described.

[0044] The (meth)acrylic resin having a succinimide structure in the main chain is, for example, a resin containing a succinimide unit represented by the following general formula (1) and a methyl methacrylate unit, and can be produced by heating and melting a polymethyl methacrylate resin and then treating it with an imidizing agent.

[0045]

[0046] (In the formula, R 1 and R 2 each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, and R 3 represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms.)

[0047] The proportion of the succinimide structure in the (meth)acrylic resin is preferably 2 to 30% by weight. When the proportion of the succinimide structure is 2% by weight or more, there is a tendency to easily impart desired heat resistance. In addition, when the proportion of the succinimide structure is 30% by weight or less, there is a tendency to be able to suppress the addition amount of the imidizing agent, suppress the odor caused by residual volatile components, and further suppress the retardation Rth in the thickness direction.

[0048] R in the above general formula (1) 3When it is methyl, the proportion of the glutarimide structure in the (meth)acrylic resin can be measured by the following method, for example. First, use 1 H-NMR BRUKER AvanceIII (400 MHz) to perform 1 1H-NMR measurement of the resin. Then, calculate the molar ratio based on the area A of the peak of the proton derived from O-CH3 constituting methyl methacrylate in the vicinity of 3.5 to 3.8 ppm and the area B of the peak of the proton derived from N-CH3 constituting the glutarimide ring in the vicinity of 3.0 to 3.3 ppm. Convert this molar ratio to weight, and thereby the proportion of the glutarimide structure can be calculated.

[0049] When manufacturing polymethyl methacrylate resin, in addition to methyl methacrylate, other monomers such as methyl acrylate, (meth)acrylic acid ethyl ester, (meth)acrylic acid butyl ester, (meth)acrylic acid isobutyl ester, (meth)acrylic acid tert-butyl ester, (meth)acrylic acid benzyl ester, (meth)acrylic acid cyclohexyl ester, etc. can be used in combination. In addition, in addition to the above, nitrile monomers such as acrylonitrile and methacrylonitrile; maleimide monomers such as maleimide, N-methyl maleimide, N-phenyl maleimide, N-cyclohexyl maleimide, etc. can be used in combination. Among them, the content rate of the acrylate unit in the polymethyl methacrylate resin is preferably less than 1% by weight, more preferably less than 0.5% by weight, and further preferably less than 0.3% by weight.

[0050] The structure of the polymethyl methacrylate resin is not particularly limited and can be any of a linear (linear) polymer, block polymer, core-shell polymer, branched polymer, ladder polymer, crosslinked polymer, etc. In the case of a block polymer, it can be any type of A-B type, A-B-C type, A-B-A type, and other types. In the case of a core-shell polymer, it can include one layer of core and one layer of shell, or the core and shell can each include multiple layers.

[0051] The manufacturing method of the polymethyl methacrylate resin is not particularly limited, and known emulsion polymerization methods, emulsion-suspension polymerization methods, suspension polymerization methods, bulk polymerization methods, solution polymerization methods, etc. can be adopted. When used in the optical field, from the aspect of less impurities, bulk polymerization method and solution polymerization method are preferred. The polymethyl methacrylate resin can be manufactured, for example, according to the methods described in Japanese Patent Laid-Open No. 56-8404, Japanese Patent Publication No. 6-86492, Japanese Patent Publication No. 7-37482, Japanese Patent Publication No. 52-32665, etc.

[0052] The manufacturing method of the (meth)acrylic resin having a glutarimide structure in the main chain includes a step (imide-forming step) of heating and melting the above-mentioned polymethyl methacrylate resin and then treating it with an imidizing agent.

[0053] The imidization agent is not particularly limited as long as it can generate the glutarimide unit represented by the above general formula (1), and substances described in International Publication No. 2005 / 054311 etc. can be used. Specifically, examples of the imidization agent include ammonia; amines having an aliphatic hydrocarbon group such as methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine; amines having an aromatic hydrocarbon group such as aniline, benzylamine, toluidine, trichloroaniline; amines having an alicyclic hydrocarbon group such as cyclohexylamine; etc. In addition, urea-based compounds that generate the amines exemplified above by heating, such as urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea, can also be used. Among these, from the viewpoints of cost and physical properties, methylamine, ammonia, and cyclohexylamine are preferred, and methylamine is more preferred. It should be noted that gaseous methylamine etc. at normal temperature can be used in a state dissolved in alcohols such as methanol.

[0054] In the imidization step, by adjusting the addition amount of the imidization agent, the ratio of the glutarimide unit and the methyl methacrylate unit in the obtained (meth)acrylic resin can be adjusted. In addition, by adjusting the degree of imidization, the physical properties of the obtained (meth)acrylic resin, the optical properties of the (meth)acrylic resin film formed from the (meth)acrylic resin, etc. can be adjusted.

[0055] The addition amount of the imidization agent is preferably 0.5 to 20 parts by weight relative to 100 parts by weight of the polymethyl methacrylate resin. When the addition amount of the imidization agent is 0.5 part by weight or more, the proportion of the glutarimide structure becomes high, and as a result, the heat resistance of the (meth)acrylic resin tends to increase and the generation of appearance defects after molding can be prevented. In addition, when the addition amount of the imidization agent is 20 parts by weight or less, there is a tendency that the imidization agent is not likely to remain in the (meth)acrylic resin, the generation of appearance defects after molding can be prevented, and foaming can be prevented.

[0056] It should be noted that in the imidization step, if necessary, in addition to adding the imidization agent, a ring-closing accelerator (catalyst) can also be added.

[0057] The method of heating and melting the polymethyl methacrylate resin and treating it with the imidization agent is not particularly limited, and all methods known in the past can be adopted. For example, by using a method such as an extruder, a batch reactor (pressure vessel), etc., the polymethyl methacrylate resin can be imidized.

[0058] When heating and melting polymethyl methacrylate resin using an extruder and treating it with an imidization agent, various extruders such as a single-screw extruder, a twin-screw extruder, and a multi-screw extruder can be used as the extruder. Among these, a twin-screw extruder is preferably used. By using a twin-screw extruder, the mixing of the imidization agent (and the imidization agent and the ring-closure promoter when using a ring-closure promoter) with the polymethyl methacrylate resin can be promoted.

[0059] Examples of the twin-screw extruder include a non-intermeshing co-rotating type, an intermeshing co-rotating type, a non-intermeshing counter-rotating type, and an intermeshing counter-rotating type. The intermeshing co-rotating type twin-screw extruder is preferably used. Since the intermeshing co-rotating type twin-screw extruder can rotate at a high speed, the mixing of the imidization agent (and the imidization agent and the ring-closure promoter when using a ring-closure promoter) with the polymethyl methacrylate resin can be further promoted.

[0060] The above-exemplified extruders can be used alone or in series. For example, a series reaction extruder described in Japanese Patent Application Laid-Open No. 2008-273140 can be used.

[0061] When performing an imidization reaction in an extruder, for example, polymethyl methacrylate resin can be introduced from the raw material input section of the extruder, melted, and after filling the barrel, the imidization agent can be injected into the extruder using an addition pump.

[0062] In this case, the temperature of the reaction zone (resin temperature) in the extruder is preferably set to 180 to 270 °C, more preferably 200 to 250 °C. When the temperature of the reaction zone (resin temperature) is 180 °C or higher, the imidization reaction tends to proceed sufficiently and the heat resistance is improved. In addition, when the temperature of the reaction zone is 270 °C or lower, the decomposition of the resin is suppressed, and as a result, the decrease in the bending resistance of the film formed from the obtained (meth)acrylic resin is suppressed. Here, the reaction zone in the extruder refers to the zone in the barrel of the extruder from the injection position of the imidization agent to the resin discharge port (die section).

[0063] By extending the reaction time in the reaction zone of the extruder, the imidization can be further advanced. The reaction time in the reaction zone of the extruder is preferably more than 10 seconds, more preferably more than 30 seconds. When the reaction time is 10 seconds or less, the imidization may hardly proceed.

[0064] The resin pressure in the extruder is preferably set to atmospheric pressure to 50 MPa, more preferably 1 to 30 MPa. When the resin pressure is 1 MPa or higher, the solubility of the imidization agent is high and the reaction further proceeds. In addition, when the resin pressure is 50 MPa or lower, no special device is required, which is preferable in terms of cost.

[0065] In the case of using an extruder, in order to remove by-products such as unreacted imidizing agent and methanol, and monomers, etc., it is preferable to install a vent hole capable of reducing the pressure below atmospheric pressure.

[0066] In the case of heating and melting polymethyl methacrylate resin and treating it with an imidizing agent using a batch reactor (pressure vessel), the structure of the batch reactor is not particularly limited. As the batch reactor, as long as it has a structure capable of melting the polymethyl methacrylate resin by heating and stirring, and capable of adding an imidizing agent (in the case of using a ring-closing accelerator, the imidizing agent and the ring-closing accelerator), a structure with good stirring efficiency is preferable. By using such a batch reactor, it is possible to prevent the polymer viscosity from increasing due to the progress of the reaction and the stirring from becoming insufficient. As a batch reactor having such a structure, for example, a stirring tank MAXBLEND manufactured by Sumitomo Heavy Industries, Ltd. can be cited.

[0067] It should be noted that reaction devices corresponding to high viscosities such as a horizontal twin-screw reaction device such as BIVOLAK manufactured by Sumitomo Heavy Industries, Ltd. and a vertical twin-screw stirring tank such as SUPERBLEND can also be appropriately used.

[0068] As a specific example of the imidization method, for example, known methods described in Japanese Patent Application Laid-Open No. 2008-273140, Japanese Patent Application Laid-Open No. 2008-274187, etc. can be cited.

[0069] The method for producing a (meth)acrylic resin having a glutarimide structure in the main chain may further include a step of treating with an esterifying agent (esterification step) on the basis of the imidization step. By this esterification step, the acid value of the imidized resin obtained in the imidization step can be adjusted within a desired range.

[0070] As the esterifying agent, for example, dimethyl carbonate, 2,2-dimethoxypropane, dimethyl sulfoxide, triethyl orthoformate, trimethyl orthoacetate, trimethyl orthoformate, diphenyl carbonate, dimethyl sulfate, methyl tosylate, methyl trifluoromethanesulfonate, methyl acetate, methanol, ethanol, methyl isocyanate, p-chlorophenyl isocyanate, dimethylcarbodiimide, dimethyl-tert-butylchlorosilane, isopropenyl acetate, dimethylurea, tetramethylammonium hydroxide, dimethyldiethoxysilane, tetra-N-butoxysilane, dimethyl(trimethylsilyl)phosphite, trimethyl phosphite, trimethyl phosphate, tricresyl phosphate, diazomethane, ethylene oxide, propylene oxide, cyclohexene oxide, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, benzyl glycidyl ether, etc. can be cited. Among these, from the viewpoints of cost, reactivity, etc., dimethyl carbonate and trimethyl orthoacetate are preferred, and dimethyl carbonate is more preferred from the viewpoint of cost.

[0071] The addition amount of the esterifying agent is preferably 0 to 12 parts by weight, more preferably 0 to 8 parts by weight, relative to 100 parts by weight of the polymethyl methacrylate resin. When the esterifying agent is within the above range, there is a tendency to be able to adjust the acid value to an appropriate range and it is difficult for the unreacted esterifying agent to remain in the resin.

[0072] In the esterification step, in addition to the esterifying agent, a catalyst can also be used in combination. As the catalyst, for example, aliphatic tertiary amines such as trimethylamine, triethylamine, tributylamine, etc. can be cited. Among these, triethylamine is preferred from the viewpoints of cost, reactivity, etc.

[0073] It should be noted that in the esterification step, only heat treatment, etc. can also be carried out without using an esterifying agent for treatment. In the case of only carrying out heat treatment (mixing and dispersing of the molten resin in the extruder), at least a part of the carboxyl groups can be made into acid anhydride groups through dehydration reactions between the carboxyl groups by-produced in the imidization step, de-alcoholization reactions between the carboxyl group and the alkyl ester group, etc. At this time, a ring-closing promoter (catalyst) can also be used. Even in the case of treatment using an esterifying agent, acid anhydridation based on heat treatment can also be carried out.

[0074] The (meth)acrylic resin having a lactone ring structure in the main chain is not particularly limited as long as it is a thermoplastic polymer having a lactone ring structure in the molecule (a thermoplastic polymer having a lactone ring structure introduced into the molecular chain), and there is no limitation on its production method. Among them, it is preferably obtained as follows: After obtaining a polymer having a hydroxyl group and an ester group in the molecular chain by polymerization (polymerization step), the obtained polymer is heat-treated to introduce a lactone ring structure into the polymer (lactonization condensation step).

[0075] In the polymerization step, a polymer having a hydroxyl group and an ester group in its molecular chain is obtained by carrying out a polymerization reaction of a monomer component containing an unsaturated monomer represented by the following general formula (2).

[0076]

[0077] (In the formula, R 4 and R 5 each independently represent a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.)

[0078] Examples of the unsaturated monomer represented by the above general formula (2) include methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, tert-butyl 2-(hydroxymethyl)acrylate, and the like. Among these, methyl 2-(hydroxymethyl)acrylate and ethyl 2-(hydroxymethyl)acrylate are preferred, and methyl 2-(hydroxymethyl)acrylate is more preferred from the viewpoint of a high heat resistance improving effect. These unsaturated monomers may be used alone or in combination of two or more.

[0079] The content of the unsaturated monomer represented by the above general formula (2) in the monomer component is preferably 5 to 50% by weight, more preferably 10 to 40% by weight, and still more preferably 10 to 30% by weight. When the content of the unsaturated monomer represented by the above general formula (2) is 5% by weight or more, the heat resistance, solvent resistance, surface hardness, etc. of the obtained resin tend to be improved. In addition, when the content of the unsaturated monomer represented by the above general formula (2) is 50% by weight or less, the occurrence of crosslinking reaction and gelation during the formation of the lactone ring structure is suppressed, and the decrease in fluidity is also suppressed. In addition, the occurrence of a situation where a volatile substance is generated and silver streaks are generated due to the residual unreacted hydroxyl group and further condensation reaction during molding is suppressed, and the increase in the retardation in the thickness direction Rth is also suppressed.

[0080] In addition to the unsaturated monomer represented by the above general formula (2), the monomer component may contain other monomers. Examples of other monomers include (meth)acrylate, hydroxyl group-containing monomers, unsaturated carboxylic acids, unsaturated monomers represented by the following general formula (3), and the like. Other monomers may be used alone or in combination of two or more.

[0081]

[0082] (In the formula, R 6 represents a hydrogen atom or a methyl group, X represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an aryl group, an -OAc group, a -CN group, or a -CO-R 7 group, Ac represents an acetyl group, R 7represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.)

[0083] As the above-mentioned (meth)acrylate, as long as it is a (meth)acrylate other than the unsaturated monomer represented by the above general formula (2), there is no particular limitation. For example, acrylate esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, benzyl acrylate, etc.; methacrylate esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, etc. Among these, from the viewpoints of heat resistance and transparency, methyl methacrylate is preferred.

[0084] When using (meth)acrylate, the content of (meth)acrylate in the monomer component is preferably 10 to 95% by weight, more preferably 10 to 90% by weight, still more preferably 40 to 90% by weight, and particularly preferably 50 to 90% by weight.

[0085] In addition to the above-mentioned (meth)acrylic resin, the (meth)acrylic resin film may further contain other thermoplastic resins. As other thermoplastic resins, olefin-based polymers, vinyl halide-based polymers, styrene-based polymers, ester-based polymers, amide-based polymers, etc. can be cited. The content of other thermoplastic resins in the (meth)acrylic resin film is preferably less than 50% by weight, more preferably less than 30% by weight.

[0086] In order to improve the mechanical strength, the (meth)acrylic resin film may contain a crosslinked elastomer. The crosslinked elastomer can be produced by known polymerization methods such as suspension polymerization, dispersion polymerization, emulsion polymerization, solution polymerization, bulk polymerization, etc.

[0087] In addition, the (meth)acrylic resin film may contain other additives as needed. As additives, for example, antioxidants; stabilizers such as light stabilizers, weather stabilizers, heat stabilizers, etc.; ultraviolet absorbers, flame retardants, antistatic agents, fillers, plasticizers, lubricants; etc.

[0088] (Manufacturing method of the film)

[0089] The manufacturing method of the (meth)acrylic resin film is not particularly limited, and methods such as injection molding, melt extrusion molding, blow molding, blow extrusion molding, compression molding, etc. can be adopted. In addition, a solution casting method or a spin coating method in which the (meth)acrylic resin is dissolved in a solvent and then formed can also be adopted. Among these, the melt extrusion method without using a solvent is preferably adopted. According to the melt extrusion method, the manufacturing cost can be reduced, and the load on the global environment and the working environment caused by the solvent can be reduced.

[0090] Hereinafter, an example of manufacturing a (meth)acrylic resin film by the melt extrusion method will be described. It should be noted that in the following description, the film obtained by the melt extrusion method is distinguished from the film obtained by other methods such as the solution casting method, and is referred to as a "melt extrusion film".

[0091] In the case of manufacturing a (meth)acrylic resin film by the melt extrusion method, first, the (meth)acrylic resin is supplied to an extruder and heated to melt.

[0092] The (meth)acrylic resin is preferably pre-dried before being supplied to the extruder. By performing such pre-drying, foaming of the resin extruded from the extruder can be prevented.

[0093] Next, the (meth)acrylic resin that has been heated and melted in the extruder is supplied to a T-die through a gear pump, a filter, etc. At this time, if a gear pump is used, the extrusion amount of the (meth)acrylic resin is uniform, and there is a tendency to reduce the thickness unevenness in the long side direction of the film. On the other hand, if a filter is used, foreign substances in the (meth)acrylic resin can be removed, and there is a tendency to obtain a (meth)acrylic resin film with an excellent appearance without defects.

[0094] Next, the (meth)acrylic resin supplied to the T-die is extruded from the T-die in the form of a sheet-like molten resin. Then, the sheet-like molten resin is sandwiched between two cooling rolls and cooled to form a film.

[0095] As the two cooling rolls for sandwiching the sheet-like molten resin, it is preferable that one is a rigid metal roll with a smooth surface, and the other is a flexible roll having a metal elastic outer cylinder with a smooth surface that can elastically deform. By sandwiching the sheet-like molten resin between the rigid metal roll and the flexible roll with the metal elastic outer cylinder and cooling to form a film, minute irregularities, die marks, etc. on the surface can be corrected, and a film with a smooth surface and a thickness unevenness of 5 μm or less can be obtained. It should be noted that in this specification, "cooling roll" is used in the sense of including "contact roll".

[0096] Even in the case of using a rigid metal roller and a flexible roller, since the surface of any cooling roller is made of metal, if the film to be formed is thin, there is a concern that the surfaces of the cooling rollers come into contact with each other, resulting in damage to the outer surface of the cooling roller and breakage of the cooling roller itself. Therefore, when forming a film by sandwiching a sheet-like molten resin between two cooling rollers, it is preferable that: first, sandwich the sheet-like molten resin between two cooling rollers for cooling, temporarily obtain a blank film with a relatively thick thickness, and then perform uniaxial stretching or biaxial stretching on the blank film to manufacture a film with a specified thickness. For example, when manufacturing a film with a thickness of 40 μm, it is preferable that: first, sandwich the sheet-like molten resin between two cooling rollers for cooling, temporarily obtain a blank film with a thickness of 150 μm, and then stretch the blank film by biaxial stretching in the longitudinal and transverse directions to manufacture a film with a thickness of 40 μm.

[0097] In this way, when the (meth)acrylic resin film is a stretched film, after forming the (meth)acrylic resin into an unstretched blank film, uniaxial stretching or biaxial stretching is performed, whereby a stretched film can be manufactured.

[0098] In order to improve the bending resistance in both the longitudinal direction (MD direction) and the width direction (TD direction) of the (meth)acrylic resin film, biaxial stretching is preferably performed.

[0099] In this specification, for the sake of convenience in description, the film that is formed into a film shape from the (meth)acrylic resin and is in an unstretched state before stretching, that is, the unstretched film, is referred to as a "blank film".

[0100] When stretching the blank film, the stretching of the blank film can be performed immediately after forming the blank film, or the blank film can be temporarily stored or moved after forming the blank film, and then the stretching of the blank film can be performed.

[0101] (Method for stretching the film)

[0102] The method for stretching the blank film is not particularly limited, and any stretching method known in the past can be adopted. For example, transverse stretching based on a tenter, longitudinal stretching based on rollers, and sequential biaxial stretching obtained by sequentially combining them can be adopted. In addition, a simultaneous biaxial stretching method for simultaneously stretching in the longitudinal and transverse directions, and a method of performing longitudinal stretching based on rollers and then transverse stretching based on a tenter can also be adopted.

[0103] There is no particular limitation on the stretching temperature when stretching the base film, and it can be appropriately determined according to the mechanical strength, surface properties, thickness accuracy, etc. required for the stretched film. Generally, when the glass transition temperature of the base film ((meth)acrylic resin) determined by the DSC method is set as Tg, it is preferably set in the temperature range of (Tg - 30°C) to (Tg + 30°C), more preferably in the temperature range of (Tg - 20°C) to (Tg + 30°C), further preferably in the temperature range of (Tg) to (Tg + 30°C), and particularly preferably in the temperature range of (Tg + 10°C) to (Tg + 30°C). When the stretching temperature is within the above temperature range, there is a tendency to reduce the thickness unevenness of the obtained stretched film and to make the mechanical properties such as elongation, tear propagation strength, and MIT bending resistance good. In addition, there is a tendency to prevent the occurrence of failures such as the film sticking to the rollers.

[0104] There is no particular limitation on the stretching ratio when stretching the base film, and it can be appropriately determined according to the mechanical strength, surface properties, thickness accuracy, etc. of the stretched film. It also depends on the stretching temperature. The stretching ratio is usually preferably selected in the range of 1.1 to 3 times, more preferably in the range of 1.3 to 2.5 times, and further preferably in the range of 1.5 to 2.3 times. When the stretching ratio is within the above range, there is a tendency to significantly improve the mechanical properties such as the elongation, tear propagation strength, and kneading fatigue resistance of the film. Therefore, a stretched film with a thickness unevenness of 5 μm or less and further an internal haze of 1.0% or less can be manufactured.

[0105] When the (meth)acrylic resin film contains a crosslinked elastomer, the mechanical strength of the film is excellent, so any of an unstretched film, a uniaxially stretched film, and a biaxially stretched film can be appropriately used.

[0106] The smaller the phase difference of the (meth)acrylic resin film, the better. Preferably, the in-plane phase difference Δnd is 5.0 nm or less, and the thickness-direction phase difference Rth is 20.0 nm or less. More preferably, Δnd is 2.0 nm or less and Rth is 5.0 nm or less. Further preferably, Δnd is 1.0 nm or less and Rth is 3.0 nm or less.

[0107] The thickness of the (meth)acrylic resin film is preferably 5 to 200 μm, more preferably 10 to 100 μm. When the thickness is 5 μm or more, there is a tendency to obtain sufficient strength. In addition, when the thickness is 200 μm or less, there is a tendency to suppress the reduction of transparency and the reduction of the drying property of the solvent (such as water) of the adhesive, and in addition, the optical film can be thinned.

[0108] The wetting tension of the surface of the (meth)acrylic resin film is preferably 40 mN / m or more, more preferably 50 mN / m or more. In order to increase the wetting tension of the surface, corona discharge treatment, plasma treatment, ozone treatment, ultraviolet irradiation, flame treatment, chemical treatment, etc. can be carried out. Among these, corona discharge treatment and plasma treatment are preferred.

[0109] In the present embodiment, it is preferable to provide a coating step such as an antireflection layer and an easy-bonding layer before stretching in a tenter. By coating before stretching in a tenter, a drying furnace does not need to be provided separately. In addition, by stretching the coating film and the substrate simultaneously, there is a tendency for the strength and the adhesion to the substrate to increase.

[0110] [Antireflection layer]

[0111] The optical film of the present embodiment has an antireflection layer on one side or both sides of the (meth)acrylic resin film. By providing the antireflection layer in this way, the reflectance of the optical film can be reduced, and the transmittance of the polarizing film when used as a polarizing element protective film can be increased.

[0112] The antireflection layer mainly consists of a binder resin having a refractive index of 1.50 or less for light with a wavelength of 594 nm and solid silica fine particles having an average primary particle size of 15 to 90 nm. The antireflection layer can be formed by coating an antireflection layer-forming composition containing a binder resin and solid silica fine particles on the (meth)acrylic resin film and then drying it.

[0113] Hereinafter, the antireflection layer-forming composition and the method for forming the antireflection layer using the antireflection layer-forming composition will be described.

[0114] The antireflection layer-forming composition can be aqueous or organic. From the viewpoints of the environment and operability, an aqueous system is preferred. Among them, in order to improve the dispersibility or solubility, or as an antifoaming agent or a leveling agent, a small amount of an organic solvent can be contained. As the organic solvent, from the viewpoints of compatibility with water and ease of treatment, an alcohol-based solvent, a ketone-based solvent, an ester-based solvent, and an ether-based solvent are preferred. As the alcohol-based solvent, methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, propylene glycol, etc. can be mentioned. As the ketone-based solvent, acetone, methyl ethyl ketone, isobutyl ketone, etc. can be mentioned. As the ester-based solvent, ethyl acetate, butyl acetate, etc. can be mentioned. As the ether-based solvent, dimethoxyethane, tetrahydrofuran, etc. can be mentioned.

[0115] As the binder resin, known water-dispersible or water-soluble polymers can be used. As examples thereof, aqueous (water-dispersible) polyurethane resins, aqueous polyester resins, aqueous (meth)acrylic resins, polyvinyl alcohol, polyvinylpyrrolidone, polycarboxylic acids, etc. can be mentioned. Among these, from the viewpoint of the adhesion to the (meth)acrylic resin film, aqueous polyurethane resins, aqueous polyester resins, and aqueous (meth)acrylic resins are preferred. These binder resins can be used alone, or two or more thereof can be used in combination.

[0116] The composition for forming an antireflection layer contains solid silica fine particles at a high concentration. Therefore, in order to achieve dispersion stabilization by the zeta potential, it is necessary to keep the pH of the composition neutral to alkaline. Therefore, the binder resin is preferably nonionic or anionic.

[0117] The aqueous polyurethane resin as the binder resin can be obtained by reacting a polyol with a polyisocyanate.

[0118] As the polyol, as long as it has two or more hydroxyl groups in the molecule, there is no particular limitation, and any suitable polyol can be used. Examples of the polyol include polyester polyols, polycarbonate diols, polyether polyols, etc.

[0119] The polyester polyol can typically be obtained by reacting a polyacid component with a polyol component. As the polyacid component, for example, aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyldicarboxylic acid, tetrahydrophthalic acid; aliphatic dicarboxylic acids such as oxalic acid, succinic acid, malonic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, linolenic acid, maleic acid, fumaric acid, mesaconic acid, itaconic acid; alicyclic dicarboxylic acids such as hexahydrophthalic acid, tetrahydrophthalic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid; reactive derivatives thereof such as acid anhydrides, alkyl esters, and acyl halides; etc. In addition, as the polyol component, ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 4,4'-dihydroxyphenylpropane, 4,4'-dihydroxymethylmethane, diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, 1,4-cyclohexanedimethanol, 1,4-cyclohexanediol, bisphenol A, bisphenol F, glycerin, 1,1,1-trimethylolpropane, 1,2,5-hexanetriol, pentaerythritol, glucose, sucrose, sorbitol, etc. can be mentioned.

[0120] The polycarbonate diol is preferably an aliphatic polycarbonate diol. The polyurethane resin synthesized from such an aliphatic polycarbonate diol not only has excellent mechanical properties, but also has excellent water resistance, oil resistance, and long-term weather resistance. In particular, it has a lower refractive index than aromatic polycarbonate diols, so it is beneficial for achieving an antireflection effect. Examples of the aliphatic polycarbonate diol include poly(hexamethylene carbonate) diol, poly(cyclohexane carbonate) diol, and the like.

[0121] The polyether polyol can typically be obtained by addition through ring-opening polymerization of an alkylene oxide in a polyol. Examples of the polyol include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, glycerin, trimethylolpropane, and the like.

[0122] The polyisocyanate is not particularly limited as long as it is a compound having two or more isocyanate groups in the molecule. Examples of the polyisocyanate include toluene diisocyanate (TDI), 4,4-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), dimethylbiphenyl diisocyanate (TODI), hexamethylene diisocyanate (HMDI), isophorone diisocyanate (IPDI), p-phenylene diisocyanate, 1,4-diisocyanate, xylylene diisocyanate (XDI), and the like.

[0123] The aqueous polyester resin as the binder resin can be obtained by polymerizing a polyol and a dicarboxylic acid using an esterification method. Alternatively, it can be obtained by polymerizing a polyol and a dicarboxylic acid diester using a transesterification method. In the production of the aqueous polyester resin, any suitable condensation reaction catalyst can also be used.

[0124] The aqueous (meth)acrylic resin as the binder resin can be obtained by polymerizing a (meth)acrylic monomer. At this time, it is preferable to use a (meth)acrylic monomer having a glass transition temperature higher than room temperature. Examples of the (meth)acrylic monomer having a glass transition temperature higher than room temperature include methyl methacrylate, ethyl methacrylate, isobutyl methacrylate, and the like. In addition, for the purpose of improving the adhesive force and the physical properties of the coating film, one or more (meth)acrylic monomers having a glass transition temperature lower than room temperature can also be mixed and used. Examples of the (meth)acrylic monomer having a glass transition temperature lower than room temperature include methoxyethylamino acrylate, butyl acrylate, hexyl acrylate, ethylhexyl acrylate, and the like.

[0125] The refractive index of the binder resin for light with a wavelength of 594 nm is 1.50 or less, preferably 1.49 or less. When the refractive index of the binder resin for light with a wavelength of 594 nm is 1.50 or less, the refractive index difference from the solid silica particles is small. Therefore, scattering at the interface with the solid silica particles is suppressed, and the transparency of the antireflection layer tends to increase. The lower limit value of the refractive index of the binder resin for light with a wavelength of 594 nm is not particularly limited and is usually 1.47 or more.

[0126] The Young's modulus of the binder resin is preferably 200 MPa or less, more preferably 100 MPa or less. When the Young's modulus of the binder resin is 200 MPa or less, even in the case of containing a large amount of solid silica particles, the flexibility of the antireflection layer can be maintained, and there is a tendency to follow stretching. The lower limit value of the Young's modulus of the binder resin is not particularly limited and is usually 1 MPa or more.

[0127] The number average molecular weight of the binder resin is preferably 5,000 to 600,000, more preferably 10,000 to 400,000. The number average molecular weight of the binder resin can be determined by polystyrene conversion using gel permeation chromatography.

[0128] In order to sufficiently reduce the refractive index of the antireflection layer and to impart anti-blocking properties to the optical film, the composition for forming the antireflection layer contains solid silica particles.

[0129] The average primary particle diameter of the solid silica particles is 15 to 90 nm, preferably 20 to 80 nm. When the average primary particle diameter of the solid silica particles is 15 nm or more, the dispersion stability in the composition for forming the antireflection layer is good, and the case where the interparticle distance in the antireflection layer becomes small and whitening occurs due to inability to follow stretching is suppressed. In addition, when the average primary particle diameter of the solid silica particles is 90 nm or less, the case where scattering occurs at the interface with the binder resin and the transparency deteriorates, and the case where halation occurs due to external haze caused by unevenness are suppressed.

[0130] It should be noted that the average primary particle diameter of the solid silica particles can be measured by dynamic light scattering method.

[0131] As the solid silica particles, commercially available colloidal silica can be used. As commercially available colloidal silica, for example, Quartron PL series manufactured by Fuso Chemical Industry Co., Ltd., SNOWTEX series manufactured by Nissan Chemical Industries, Ltd., AERODISP series and AEROSIL series manufactured by NIPPON AEROSIL CO., LTD. etc. can be cited.

[0132] The content rate of solid silica fine particles in the solid component of the composition for forming an antireflection layer is 30 to 80% by weight, preferably 40 to 70% by weight, and more preferably 50 to 60% by weight. When the content rate of the solid silica fine particles is 30% by weight or more based on the solid component, the refractive index of the formed antireflection layer is sufficiently reduced, and there is a tendency to exhibit desired antireflection performance. In addition, when the content rate of the solid silica fine particles is 80% by weight or less based on the solid component, there is a tendency to suppress the case where the formed antireflection layer hardens and cannot follow the stretching, resulting in whitening due to cracks.

[0133] It should be noted that in order to achieve the desired antireflection performance, in addition to the solid silica fine particles, hollow silica fine particles, hollow polymer fine particles, etc. can also be used in combination.

[0134] The composition for forming an antireflection layer may contain a crosslinking agent. For example, when the binder resin has a carboxyl group, as the crosslinking agent, a polymer having a group capable of reacting with the carboxyl group is preferably used. Examples of the group capable of reacting with the carboxyl group include an organic amino group, an oxazoline group, an epoxy group, a carbodiimide group, etc. Among these, the crosslinking agent having an oxazoline group has a long pot life at room temperature when mixed with the binder resin and undergoes a crosslinking reaction by heating, so the operability is good.

[0135] In addition, the composition for forming an antireflection layer may further contain optional additives. Examples of the additives include a dispersion stabilizer, a thixotropic agent, an antioxidant, an ultraviolet absorber, an antifoaming agent, a thickener, a dispersant, a surfactant, a catalyst, a filler, a lubricant, an antistatic agent, etc.

[0136] The solid component concentration in the composition for forming an antireflection layer is preferably 1.5 to 15% by weight, and more preferably 2 to 10% by weight. When the solid component concentration is 1.5% by weight or more, there is a tendency for the drying time to become shorter and the productivity to increase. In addition, when the solid component concentration is 15% by weight or less, there is a tendency for bubbles to be easily discharged and the pot life to become longer.

[0137] The thickness of the antireflection layer is preferably 50 to 300 nm. When the thickness of the antireflection layer is 50 nm or more, there is a tendency to obtain a sufficient antireflection effect. In addition, when the thickness of the antireflection layer is 300 nm or less, there is a tendency to suppress the occurrence of iridescence due to the interference light in the visible light region.

[0138] Based on the theory of thin film interference of a single-layer film, when the thickness d of the antireflection layer satisfies the following formula, the reflectance is minimized due to the interference of the surface reflected light and the reflected light of the substrate. In the formula, λ represents the wavelength of the irradiated light, and n2 represents the refractive index of the antireflection layer.

[0139] d = (1 / 4) × (λ / n2)

[0140] If λ is set to 550 nm and n2 is set to 1.46, then d = 94 nm is the optimum value. Actually, on the basis of considering the above formula, uneven thickness, the strength of the coating film, etc. can be taken into account, and the thickness can be set within the above range.

[0141] It is preferable to hydrophilize the surface of the (meth)acrylic resin film in advance by corona discharge treatment, plasma treatment, etc. before coating the antireflection layer-forming composition.

[0142] The coating method of the antireflection layer-forming composition is not particularly limited, and a bar coating method, a roll coating method, an intaglio coating method, a rod coating method, a slot die coating method, a curtain coating method, a spray column coating method, etc. can be adopted.

[0143] The drying temperature after coating the antireflection layer-forming composition is preferably 50 °C or higher, more preferably 80 °C or higher.

[0144] [Easy-to-bond layer]

[0145] The optical film of the present embodiment may have an easy-to-bond layer for improving the adhesiveness to a polarizing member on the surface on the side opposite to the antireflection layer. As the easy-to-bond layer, for example, a layer formed by coating a composition mainly composed of a polyurethane resin having a carboxyl group as described in Japanese Patent No. 5354733 can be cited.

[0146] It should be noted that when antireflection layers are formed on both sides of the optical film of the present embodiment, one of the antireflection layers can also be used as the easy-to-bond layer.

[0147] [Polarizing film]

[0148] The polarizing film of the present embodiment is formed by laminating the above-described optical film of the present embodiment on a polarizing member via an adhesive layer.

[0149] As the polarizing member, an appropriate polarizing member that meets the purpose can be adopted. As the polarizing member, for example, those obtained by adsorbing dichroic substances such as iodine and dichroic dyes on hydrophilic polymer films such as polyvinyl alcohol-based films, partially formaldehydeized polyvinyl alcohol-based films, and ethylene-vinyl acetate copolymer-based partially saponified films and performing uniaxial stretching; polyolefin-based oriented films such as dehydrated products of polyvinyl alcohol and dehydrochlorinated products of polyvinyl chloride; etc. Among these, from the viewpoint of a high polarization dichroism ratio, a polarizing member obtained by adsorbing a dichroic substance such as iodine on a polyvinyl alcohol-based film and performing uniaxial stretching is preferred. The thickness of the polarizing member is not particularly limited, and is usually about 1 to 80 μm.

[0150] The adhesive for forming the adhesive layer is not particularly limited, and any adhesive such as a polyvinyl alcohol-based adhesive, an acrylic-based adhesive, a polyurethane-based adhesive, an isocyanate-based adhesive, an epoxy-based adhesive, or a melamine-based adhesive can be used.

[0151] Figure 1 Fig. shows a schematic cross-sectional view showing an example of the layer structure of the polarizing film of the present embodiment. Figure 1 The polarizing film 10 shown has a laminated structure in which polarizing element protection films 30 and 40 are respectively adhered to both sides of the polarizing element 20 via adhesive layers 51 and 52.

[0152] The polarizing element protection film 30 sequentially has an easy-to-bond layer 31, a (meth)acrylic resin film 32, and an antireflection layer 33 from the side of the polarizing element 20. In addition, the polarizing element protection film 40 sequentially has an easy-to-bond layer 41 and a (meth)acrylic resin film 42 from the side of the polarizing element 20. The polarizing element protection film 40 may have an adhesive layer (not shown) for bonding to a liquid crystal cell or the like on the surface opposite to the polarizing element 20.

[0153] Figure 1 In the polarizing film 10 shown, the above-described optical film of the present embodiment is used as the polarizing element protection film 30.

[0154] <Image display device>

[0155] The image display device of the present embodiment includes the above-described polarizing film of the present embodiment. Examples of the image display device include a liquid crystal display device (LCD).

[0156] The liquid crystal display device includes a liquid crystal cell and a backlight unit as a light source, and includes polarizing films disposed on both sides (the backlight unit side and the visual recognition side) of the liquid crystal cell. The polarizing film of the present embodiment can be used on either the backlight unit side or the visual recognition side. When used as the polarizing film on the backlight unit side, by arranging it with the antireflection layer facing the backlight unit side, the reflectance can be reduced and the brightness of the liquid crystal display can be increased. On the other hand, when used as the polarizing film on the visual recognition side, by making the antireflection layer the outermost layer, the surface reflected light can be reduced and the visual recognition property of the liquid crystal display can be improved.

[0157] Figure 2 Fig. shows a schematic cross-sectional view showing an example of the layer structure of the liquid crystal display device of the present embodiment. Figure 2The liquid crystal display device 100 shown includes: a liquid crystal cell 110, a front-side polarizing film 160a laminated on the visual recognition side of the liquid crystal cell 110 via an adhesive layer 170a, a back-side polarizing film 160b laminated on the side opposite to the visual recognition side of the liquid crystal cell 110 via an adhesive layer 170b, and a backlight unit 180 disposed outside the back-side polarizing film 160b.

[0158] The front-side polarizing film 160a has a laminated structure in which polarizing film protection films 130a and 140a are respectively adhered to both sides of a polarizer 120a via adhesive layers 151a and 152a. The polarizing film protection film 130a on the side far from the liquid crystal cell 110 has, in order from the polarizer 120a side, an easy-adhesion layer 131a, a (meth)acrylic resin film 132a, and an antireflection layer 133a. In addition, the polarizing film protection film 140a on the liquid crystal cell 110 side has, in order from the polarizer 120a side, an easy-adhesion layer 141a and a (meth)acrylic resin film 142a.

[0159] The back-side polarizing film 160b has a laminated structure in which polarizing film protection films 130b and 140b are respectively adhered to both sides of a polarizer 120b via adhesive layers 151b and 152b. The polarizing film protection film 130b on the side far from the liquid crystal cell 110 has, in order from the polarizer 120b side, an easy-adhesion layer 131b, a (meth)acrylic resin film 132b, and an antireflection layer 133b. In addition, the polarizing film protection film 140b on the liquid crystal cell 110 side has, in order from the polarizer 120b side, an easy-adhesion layer 141b and a (meth)acrylic resin film 142b.

[0160] In Figure 2 In the liquid crystal display device 100 shown, the optical films of the present embodiment are used as the polarizing film protection films 130a and 130b.

[0161] [Examples]

[0162] Hereinafter, the present invention will be described more specifically based on examples and comparative examples, but the present invention is not limited to the following examples.

[0163] The measurement methods of various physical properties described in the examples and comparative examples are as follows.

[0164] (Haze)

[0165] The haze of the optical film is measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., NDH2000) in accordance with JIS K7136.

[0166] (Total transmittance)

[0167] The total light transmittance of the optical film was measured in accordance with JIS K7361-1 using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., NDH2000).

[0168] (Young's modulus of the binder resin)

[0169] The aqueous dispersion of polyurethane resin as the binder resin was poured into a glass container so that the film thickness after drying would be 100 μm, and it was left at room temperature for 24 hours. Then, it was dried at 50 °C for 3 hours and at 120 °C for 20 minutes to obtain a sheet of polyurethane resin. The obtained sheet of polyurethane resin was punched into a dumbbell shape according to JIS K7162 to obtain a test piece. For this test piece, a tensile tester (manufactured by Instron Japan Co., Ltd., tensile testing machine 5564) was used to conduct a tensile test at a tensile speed of 5 mm / min, and the Young's modulus was measured based on the slope of the obtained SS curve.

[0170] (Refractive index of the binder resin)

[0171] For the test piece obtained by the above measurement of the Young's modulus, a prism coupler (manufactured by Metricon, Model 2010) was used to measure the refractive index of light with a wavelength of 594 nm.

[0172] (Calculation of the proportion of the glutarimide structure in the (meth)acrylic resin)

[0173] The proportion of the glutarimide structure in the (meth)acrylic resin was calculated as follows. First, 1 1H-NMR BRUKER AvanceIII (400 MHz) was used to conduct 1H-NMR measurement of the (meth)acrylic resin. 1 Then, the molar ratio was calculated from the area A of the peak of the proton derived from O-CH3 constituting methyl methacrylate in the vicinity of 3.5 to 3.8 ppm and the area B of the peak of the proton derived from N-CH3 constituting the glutarimide ring in the vicinity of 3.0 to 3.3 ppm. The molar ratio was converted to weight to calculate the proportion of the glutarimide structure.

[0174] (Glass transition temperature)

[0175] Using a differential scanning calorimeter DSC7020 (manufactured by SII), 10 mg of the (meth)acrylic resin was heated at a heating rate of 20 °C / min in a nitrogen atmosphere, and the glass transition temperature was determined by the midpoint method.

[0176] <Production Example 1: Production of (meth)acrylic resin>

[0177] As the extruder, a meshing co-rotating twin-screw extruder with a diameter of 40 mm (L / D = 90) was used. The set temperature of each temperature control zone of the extruder was set to 250 - 280 °C, and the screw rotation speed was set to 85 rpm. The polymethyl methacrylate resin was melted by a kneading block. After being filled, 1.8 parts by weight of monomethylamine (manufactured by Mitsubishi Gas Chemical Company, Inc.) relative to 100 parts by weight of the polymethyl methacrylate resin was injected from the nozzle. The resin coming out in the form of a wire from the die provided at the extruder outlet was cooled in a water tank and then pelletized by a pelletizer to obtain resin (I). Next, the set temperature of each temperature control zone of the meshing co-rotating twin-screw extruder with a diameter of 40 mm was set to 240 - 260 °C. 0.56 parts by weight of dimethyl carbonate relative to 100 parts by weight of the polymethyl methacrylate resin was injected from the nozzle to reduce the carboxyl groups in resin (I). Furthermore, the by-products and excess dimethyl carbonate after the reaction were removed. The resin coming out in the form of a wire from the die provided at the extruder outlet was cooled in a water tank and then pelletized by a pelletizer to obtain a (meth)acrylic resin 1 having a glutarimide structure in the main chain. The glass transition temperature of the (meth)acrylic resin 1 was 123 °C, and the proportion of the glutarimide structure was 6% by weight.

[0178] <Production Example 2: Production of (meth)acrylic resin film>

[0179] After drying the (meth)acrylic resin 1 obtained in Production Example 1 at 100 °C for 5 hours, a film was produced using a meshing co-rotating twin-screw extruder with a diameter of 15 mm (L / D = 45) equipped with a T-die at the extruder outlet. The sheet-like molten resin extruded from the T-die was cooled by a cooling roll to obtain a blank film with a width of 160 mm and a thickness of 160 μm. At this time, the surface in contact with the casting roll was defined as surface B, and the other surface was defined as surface A.

[0180] <Example 1>

[0181] 7.6 g of colloidal silica (manufactured by Fuso Chemical Industry Co., Ltd., Quartron PL-03, average primary particle size: 35 nm, solid content: 20%) was put into a glass container, 25.5 g of pure water and 0.5 g of 1% ammonia water were added, and it was stirred with a magnetic stirrer for 10 minutes. Next, as a binder resin, 4 g of an aqueous polyurethane resin (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., SUPERFLEX 460, solid content: 38%) was added and stirred for 10 minutes to prepare a composition for forming an antireflection layer. The overall solid content concentration of this composition for forming an antireflection layer was 8% by weight, and the content rate of solid silica fine particles in the solid content was 50% by weight.

[0182] The A side of the (meth)acrylic acid-based thin film obtained in Production Example 2 was subjected to corona discharge treatment, and the antireflection layer-forming composition was applied using a rod coater (#5) to form a coating film. Thereafter, the thin film was put into a hot air dryer (100 °C) and dried for 3 minutes to produce a coated blank having an antireflection layer thickness of 800 nm. Next, the obtained coated blank was simultaneously biaxially stretched using a biaxial stretching device (manufactured by Iwamoto Seisakusho Co., Ltd., IMC-1905) under the conditions of a stretching ratio of 2 times (longitudinal / transverse) and 145 °C to produce an optical thin film having an antireflection layer thickness of 200 nm. Then, the haze and total light transmittance of the obtained optical thin film were measured. The results are shown in Table 1.

[0183] <Examples 2 to 5, Comparative Examples 2 to 6>

[0184] The composition of the antireflection layer-forming composition was changed as shown in Table 1, and an optical thin film was produced in the same manner as in Example 1 except for this. Then, the haze and total light transmittance of the obtained optical thin film were measured. The results are shown in Table 1.

[0185] An antireflection layer-forming composition was not applied, and an optical thin film was produced in the same manner as in Example 1 except for this. Then, the haze and total light transmittance of the obtained optical thin film were measured. The results are shown in Table 1.

[0186] It should be noted that the abbreviations in Table 1 have the following meanings, respectively.

[0187] · SF460 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., SUPERFLEX460)

[0188] · SF420NS (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., SUPERFLEX420NS)

[0189] · PL-3 (manufactured by Fuso Chemical Industry Co., Ltd., Quartron PL-3)

[0190] · PL-7 (manufactured by Fuso Chemical Industry Co., Ltd., Quartron PL-7)

[0191] · ST-30 (manufactured by Nissan Chemical Industries, Ltd., SNOWTEX ST-30)

[0192] · ST-1040 (manufactured by Nissan Chemical Industries, Ltd., SNOWTEX ST-1040) [Table 1]

[0193]

[0194] As can be seen from the results in Table 1, by setting the refractive index and Young's modulus of the binder resin within a specified range and setting the content rate of the solid silica fine particles within a specified range, an optical film with a high total light transmittance and a low haze can be obtained.

Claims

1. An optical film having an antireflection layer formed on one or both sides of a (meth)acrylic resin film containing a (meth)acrylic resin. The antireflection layer contains a binder resin having a refractive index of 1.50 or less for light with a wavelength of 594 nm and solid silica fine particles having an average primary particle diameter of 15 to 90 nm. The content of the solid silica fine particles in the solid components of the antireflection layer is 30 to 80% by weight. The total light transmittance of the optical film is 93% or more, and the haze is 2% or less.

2. The optical thin film according to claim 1, wherein, The Young's modulus of the binder resin is 200 MPa or less.

3. The optical thin film according to claim 1, wherein, The thickness of the antireflection layer is 50 to 300 nm.

4. The optical thin film according to claim 1, wherein, The (meth)acrylic resin film contains a (meth)acrylic resin having a ring structure in the main chain.

5. The optical thin film according to claim 4, wherein, The ring structure is at least one selected from a succinimide structure, a lactone ring structure, a maleic anhydride structure, an N-substituted maleimide structure, and a glutaric anhydride structure.

6. A polarizing film in which the optical film according to any one of claims 1 to 5 is laminated on a polarizing member via an adhesive layer.

7. An image display device having the polarizing film according to claim 6.

8. A liquid crystal display device comprising: a liquid crystal cell; a front-side polarizing film laminated on the visual recognition side of the liquid crystal cell via an adhesive layer; a back-side polarizing film laminated on the side opposite to the visual recognition side of the liquid crystal cell via an adhesive layer; and a backlight unit disposed outside the back-side polarizing film, wherein each of the front-side polarizing film and the back-side polarizing film has a polarizing member and polarizing member protective films disposed on both sides of the polarizing member, and the polarizing member protective film of the back-side polarizing film disposed on the backlight unit side is the optical film according to any one of claims 1 to 5, and the antireflection layer of the optical film is located on the backlight unit side.

Citation Information

Patent Citations

  • JP1977032665B2

  • Preparation of polymer particle containing little foreign matter

    JP1981008404A

  • Novel method for producing methacrylic polymer

    JP1994086492B2

  • Method for producing methacrylic polymer

    JP1995037482B2

  • Manufacturing method for thermoplastic resin, and thermoplastic resin

    JP2008273140A